Effectiveness of simulation debriefing methods in nursing education: A systematic review and meta-analysis. (December 2021) - Niu, Yushuo; Liu, Ting; Li, Kuinan; Sun, Mengke; Sun, Yaru; Wang, Xin; Yang, Xiuling
Abstract: Objective: This systematic review and meta-analysis aimed to evaluate debriefing methods' effectiveness on learning outcomes for nursing students. Design: A systematic review and meta-analysis were applied according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement. Data sources: Publications were searched in PubMed, EMBASE, The Cochrane Library, Web of Science, China National Knowledge Infrastructure, and WANFANG (China) databases from inception to 2020. Review methods: Two researchers independently retrieved articles and evaluated their quality. Review Manager version 5.3 software was used to conduct the meta-analysis, following the PRISMA guidelines. Bias risk was assessed using the Joanna Briggs Institute manual. Heterogeneity was assessed by I 2 statistics. Standardized mean difference (SMD) and 95% confidence intervals (CIs) were used for effect size analysis based on learning outcomes. Results: Sixteen studies were selected in the systematic review and 13 studies with 1637 nursing students were included in the meta-analysis. Five debriefing methods were used in the intervention group. The analysis showed that Debriefing for Meaningful Learning was more effective on the debriefing quality (SMD = 0.52, 95%CI [0.32, 0.72]), and that video-assisted debriefing was more effective on nursing students' experiences (SMD = 0.30, 95%CI [0.02, 0.58]) and critical thinking (SMD = 0.90, 95%CI [0.65, 1.15]) compared with the usual debriefing. However, written debriefing did not show better effects on students' experiences (SMD = −0.22, 95%CI [−0.51, 0.07]), and peer-led debriefing did not show better effects on the debriefing quality compared with the usual debriefing (SMD = −0.15, 95%CI [−1.43, −0.67]). Conclusions: The study indicated that Debriefing for Meaningful Learning and video-assisted debriefing showed a positive impact on nursing education. Future studies that have larger sample sizes, high-quality debriefing methods, robust study designs, and other learning outcomes are required. Highlights: There are many kinds of debriefing methods in nursing education. Debriefing for Meaningful Learning (DML) and video-assisted debriefing had a positive effect compared with usual debriefing. The effectiveness of written and peer-led debriefing was not significant compared with usual debriefing.